Mechanisms of recovery: Community perceptions of change and growth following multiple disasters - Osofsky, Howard; Osofsky, Joy; Saltzman, Leia Y.; Lightfoot, Estilla; De King, Jule; Hansel, Tonya C. (Frontiers in Psychology, 2022)
Introduction and Purpose: The geographic location of the Gulf South leaves communities in continuous threat, response, and recovery disaster cycles. Hurricane Katrina in 2005 provided an opportunity to study disaster mental health. Less than 5 years after the storm, many Hurricane Katrina survivors were impacted again by the Deepwater Horizon Gulf oil spill. Despite adversities impacting Gulf communities, over 90% of participants reported they were resilient. The purpose of this study was to improve the understanding of the mechanisms that contribute to strengths following adversity in communities affected by repeated disasters. Specifically, we focused on survivor perceptions of personal, spiritual, or community changes in efforts to describe community resilience and posttraumatic growth (PTG). Methods: Participants were recruited through a quantitative survey and community flyers. Participants represented southeastern Louisiana, in areas impacted by hurricanes and the oil spill—for a total of 5 focus groups and 41 participants. Focus groups began by asking each participant to provide a brief overview of their disaster survival story and three additional guiding strengths-based questions. Data were transcribed using Dragon Speech Recognition software. A total of 963 unique responses were analyzed and coded. Results: The following themes were identified: connectedness (n = 259), coping (n = 94); spirituality (n = 60), adaptability (n = 47) and self-reliance (n = 23). Participants noted a growth mindset from the disasters and also acknowledged coinciding negative experiences (n = 154) associated with community change and loss, where subthemes included change in connectedness (n = 97), crime (n = 26), and feeling like an outsider (n = 31). Discussion and Implications: These findings help scholars and mental health practitioners better understand the lived experiences of PTG in a community of survivors impacted by recurring traumatic experiences. In keeping with previous literature, PTG and negative experiences associated with trauma are not mutually exclusive but occur simultaneously. Our results offer a holistic picture of coping with cumulative or repeated traumas and suggest that connectedness, coping, and spirituality provide important buffers to negative psychosocial outcomes.